Fungaemia due to rare yeasts in paediatric intensive care units: A prospective study. Issue 11 (20th May 2021) - Kaur, Harsimran; Singh, Shreya; Rudramurthy, Shivaprakash Mandya; Jayashree, Muralidharan; Peters, Nitin James; Ray, Pallab; Samujh, Ram; Ghosh, Anup; Chakrabarti, Arunaloke
Abstract: Background: Considering the emergence of fungaemia due to rare yeasts at our centre, we performed a systematic epidemiologic study on fungaemia due to rare yeast. Objectives: We undertook the present prospective observational study to explore the epidemiological features and clinical characteristics of fungaemia due to rare yeasts in paediatric ICUs at our centre. Methods: The successive yeasts isolated from blood at our PICUs during December 2017 through March 2019 were identified by molecular methods. Fungaemia due to yeasts other than C. albicans, C. tropicalis, C. glabrata, C. krusei and C. parapsilosis was categorised as rare yeasts. Antifungal susceptibility testing of the yeast isolates was performed as per clinical and laboratory standards institute (CLSI) guidelines. We also compared different clinical parameters of fungaemia due to common versus rare yeasts, and rare yeasts in neonates versus non‐neonates. Results: During the study period, 212 yeast isolates were obtained from 159 patients at PICUs of our hospital, and 127 isolates from 98 patients (61.6%) were categorised as rare yeasts. Neonates acquired fungaemia significantly earlier after ICU admission than non‐neonates (median:4 vs 6 days; p  = .005). Regarding epidemiology study of rare yeast fungaemia, Wickerhamomyces anomalus (43.8%) and Candida utilis (40.8%) were common isolates; surgical intervention and gastrointestinal disease were significantly associated; overall, azole, echinocandin and amphotericin B resistance was at 9.1%, 1.02% and 1.02%, respectively; overall mortality was 65.3%. Conclusions: The emergence of rare yeasts especially W. anomalus and C. utilis causing fungaemia in our children demands urgent attention to control the spread.